2022
DOI: 10.1002/adsu.202100321
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Catalysis of Co‐Zr/CNx Bimetallic Nanoparticles Enables Reductive Amination of Biobased Levulinic Acid

Abstract: Bimetallic synergy and carbon–nitrogen doping can contribute to enhanced catalytic activity due to the strong electronic state and unique geometrical structure. In this work, a series of biomass‐derived Co‐M bimetallic CN doped catalysts (Co‐M@Chitosan‐X; M = Zr, Ni, Fe, Cu, In; X denotes the molar percentage of M) are prepared via simple oil bath reflow and annealing. The Co‐Zr@Chitosan‐X catalysts are determined to contain alloys (Co‐Zr), metal‐carbon bonds (Co‐C, Zr‐C), metal‐nitrogen bonds (Co‐N, Zr‐N), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…N-doped mesoporous carbon (NMC) has attracted a lot of attention and is used as a catalyst carrier due to its adjustable pore size and functionalization, high surface area, good hydrothermal stability, and electron conduction. Moreover, the replacement of the C atom by a N atom can lower the valence band, increase the chemical stability of the material, and increase the electron density at the Fermi energy level. , According to our previous study, NMC-embedded Ru showed excellent catalytic performance for the hydrogenolysis of LA to GVL, where the weak basicity of the N dopant may promote the adsorption of acidic LA and consequently accelerate the following hydrogenolysis reaction. This inspired us to design and develop a novel NMC-supported Ru multifunctional catalyst for the reductive amination of LA/esters with amines.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…N-doped mesoporous carbon (NMC) has attracted a lot of attention and is used as a catalyst carrier due to its adjustable pore size and functionalization, high surface area, good hydrothermal stability, and electron conduction. Moreover, the replacement of the C atom by a N atom can lower the valence band, increase the chemical stability of the material, and increase the electron density at the Fermi energy level. , According to our previous study, NMC-embedded Ru showed excellent catalytic performance for the hydrogenolysis of LA to GVL, where the weak basicity of the N dopant may promote the adsorption of acidic LA and consequently accelerate the following hydrogenolysis reaction. This inspired us to design and develop a novel NMC-supported Ru multifunctional catalyst for the reductive amination of LA/esters with amines.…”
Section: Introductionmentioning
confidence: 97%
“…Currently, pyrrolidones are industrially produced by the reaction of γ-butyrolactone with the corresponding amines or by the dehydrogenation–amination of butanediol with suitable amines under harsh reaction conditions (>200 °C) . In contrast to these industrial methods using fossil resources, reductive amination of the renewable, readily available, and biomass-derived platform molecule LA with amines offers a sustainable production route for N -substituted 5-methyl-2-pyrrolidones. ,, In general, there are two common reaction pathways (Scheme ). In one pathway (path 1), initially, the intermediate imine a was easily generated through the nucleophilic attack of the −NH 2 group to the CO group of LA/esters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An excellent heterogenous catalytic system was developed by Shimizu and co-workers, where they demonstrated the amination with a wide range of amines with generally high yields and no solvent . Another example used Zr-Co catalysts prepared using chitosan as a carbon and nitrogen source to generate 5-methyl-2-pyrrolidone with a 93% yield . Homogenous catalysts were first reported in 2011 with the use of a ruthenium catalyst and formic acid .…”
Section: Cyclic Monomersmentioning
confidence: 99%
“…For example, 5‐methyl‐2‐pyrrolidone (MPD) can be obtained by reductive amination of LA/ester in H 2 and ammonia gas or NH 3 ⋅H 2 O [10] . However, an excessive hydrogen pressure (30‐50 bar) is required in this process [10a,11] . To avoid high H 2 pressure, one synthesis technique of MPD is by using HCOOH as H source.…”
Section: Introductionmentioning
confidence: 99%